A roadmap for investigating the role of the prion protein in depression associated with neurodegenerative disease. Issue 2 (3rd March 2016) - Beckman, Danielle; Linden, Rafael
ABSTRACT: The physiological properties of the native, endogenous prion protein (PrP C ) is a matter of concern, due to its pleiotropic functions and links to neurodegenerative disorders and cancer. In line with our hypothesis that the basic function of PrP C is to serve as a cell surface scaffold for the assembly of signaling modules, multiple interactions have been identified of PrP C with signaling molecules, including neurotransmitter receptors. We recently reported evidence that PrP C may modulate monoaminergic neurotransmission, as well as depressive-like behavior in mice. Here, we discuss how those results, together with a number of other studies, including our previous demonstration that both inflammatory and behavioral stress modulate PrP C content in neutrophils, suggest a distributed role of PrP C in clinical depression and inflammation associated with neurodegenerative diseases. An overarching understanding of the multiple interventions of PrP C upon physiological events may both shed light on the pathogenesis of, as well as help the identification of novel therapeutic targets for clinical depression, Prion and Alzheimer's Diseases.